To study the laboratory profile of severe malaria in a tertiary care centre of North India - Rahul Sood; Rajamanickam Timothy; Navjot Singh (International Journal of Medical Research and Review, 2016)
Introduction: Malaria ranks third among the major infectious diseases in causing deaths- after pneumococcal acute respiratory infections and tuberculosis. It is expected that by the turn of the century malaria would be the number one infectious killer disease in the world. It is the most widely distributed and is responsible for up to 400 million infections every year. The aim of the study was to describe the laboratory parameters and their correlation with mortality in Malaria.Methods: This was a one year retrospective and one and half year prospective study. All patients diagnosed to have Malaria were included in this study.Results: Laboratory parameters were recorded carefully and the data was analyzed by the appropriate statistical methods. A total of 124 patients were studied 92 patients of Plasmodium vivax, 21 patients of Plasmodium falciparum and 11 patients of Mixed malaria. Complications observed were severe anemia(< 7 gm/dl), thrombocytopenia, renal dysfunction (S.creat > 1.2mg/dl), raised bilirubin > 3mg%, metabolic acidosis, and acute respiratory distress syndrome (ARDS). Thrombocytopenia and jaundice were the most frequent complications in the severe cases. 10/124 patients (8.06%) expired. 8/10 patients who expired had four or more organ dysfunction.Conclusion: ARDS had the most significant correlation with mortality. Other significant factors contributing to death were jaundice, severe anemia and renal failure.